All-fiber fourth and fifth harmonic generation from a single source - Khudus, M.I.M.A.; Lee, T.; De Lucia, F.; Corbari, C.; Sazio, P.; Horak, P.; Brambilla, G. (Optical Society of America, 2016)
All-fiber fourth and fifth harmonic generation from a single source is demonstrated experimentally and analyzed theoretically. Light from a fully fiberized high power master oscillator power amplifier is launched into a periodically poled silica fiber generating the second harmonic. The output is then sent through two optical microfibers that generate the third and fourth harmonic, respectively, via four wave mixing (FWM). For a large range of pump wavelengths in the silica optical transmission window, phase matched FWM can be achieved in the microfibers at two different diameters with relatively wide fabrication tolerances of up to +/-5 nm. Our simulations indicate that by optimizing the second harmonic generation efficiency and the diameters and lengths of the two microfibers, conversion efficiencies to the fourth harmonic in excess of 25% are theoretically achievable.